"Caste in Everyday Life: Experience and Affect in Indian Society", edited by Dhaneswar Bhoi and Hugo Gorringe - Lee, Joel ca. 20./21. Jh. (Religions of South Asia, 2025)
Caste in Everyday Life: Experience and Affect in Indian Society, edited by Dhaneswar Bhoi and Hugo Gorringe. Cham, Switzerland: Palgrave Macmillan, 2024. xxvi + 340 pp., £ 109.99 (hb), £ 39.99 (pb). ISBN 9783031306549 (hb); 9783031306570 (pb); 9783031306556 (ebook).